Athlete wellbeing in high performance settings: A scoping review - Scott, M.; Jaekel, H. R.; Crozier, A. J.; Nelson, M. J.; Ridgers, N. D. (Journal of Science and Medicine in Sport, 2025)
Objectives Athlete wellbeing is important in high-performance sport for sustaining performance and ensuring long-term personal and professional fulfilment. However, no standard definition of athlete wellbeing currently exists. This scoping review examined how international multi-sport high-performance sport organisations (HPSOs) define and operationalise athlete wellbeing.